2008
DOI: 10.1590/s0103-50532008000600009
|View full text |Cite
|
Sign up to set email alerts
|

Determination of pesticides multiresidues in shallow groundwater in a cotton-growing region of Mato Grosso, Brazil

Abstract: Foi desenvolvido um método multirresíduos empregando CLAE/DAD para a determinação de doze pesticidas em águas subterrâneas em lavouras de algodão, baseado em extração em fase sólida, utilizado como adsorvente o copolímero estireno divinilbenzeno (SDVB). O método foi validado e obtiveram-se recuperações entre 73 e 113%, desvio padrão relativo entre 2 e 16% e limites de detecção variando de 0,06 a 0,57 µg L -1. O método foi aplicado em 110 amostras de águas subterrâneas de lavouras de algodão localizadas em Prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(17 citation statements)
references
References 17 publications
(20 reference statements)
1
10
0
3
Order By: Relevance
“…The limits of detection (LOD) and quantification (LOQ) were estimated by the ratio between the standard deviation of the intercept (s) and the slope of the analytical curves (S), being LOD equal to 3 times and LOQ to 10 times the s/S ratio. Low instrumental limits of detection (LOD i < 3.0 µg L -1 ) and quantification (LOQ i < 10.0 µg L -1 ) were achieved, similar to those described in the literature, [40][41][42][43] recalling that until then, no preconcentration step was performed. Furthermore, suitable linearity (r > 0.9997) was obtained in the studied LR for all compounds.…”
Section: Chromatographic Analyses and Standard Calibrationsupporting
confidence: 68%
“…The limits of detection (LOD) and quantification (LOQ) were estimated by the ratio between the standard deviation of the intercept (s) and the slope of the analytical curves (S), being LOD equal to 3 times and LOQ to 10 times the s/S ratio. Low instrumental limits of detection (LOD i < 3.0 µg L -1 ) and quantification (LOQ i < 10.0 µg L -1 ) were achieved, similar to those described in the literature, [40][41][42][43] recalling that until then, no preconcentration step was performed. Furthermore, suitable linearity (r > 0.9997) was obtained in the studied LR for all compounds.…”
Section: Chromatographic Analyses and Standard Calibrationsupporting
confidence: 68%
“…For example, Leandro et al detected AAP in shallow groundwater in a cotton-growing region of Mato Grosso, Brazil. 7 Anderson et al reported AAP detection in the playa wetlands of Texas. 8 Wu et al detected AAP at a concentration of 0.2 mg L À1 in the Jingmi River, Beijing, China.…”
Section: Introductionmentioning
confidence: 99%
“…Diuron residues in water was analysed according to the method described by Carbo et al (2008). Aliquots of 500 ml of the samples were extracted in a SDVB cartridge (Envi-Chrom P, Supelco) previously conditioned with methanol.…”
Section: Analysis Of Pesticides Residues By Liquid Chromatographicmentioning
confidence: 99%
“…regions with cotton industry several pesticides have been detected in surface water and among the innumerous factors that affect pesticides runoff, the agricultural management system is a very important one (Carbo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation